Peningkatan Kapasitas Kurikulum 2013 Pendidikan Usia Dini Pada Guru dan Pengelola PAUD Al Birru Nasyiatul Aisyiyah - Risni Julaeni Yuhan; Diah Puspitarini; Husnul Khotimah; Lia Karisma; Fauzah Romadhon K; Hanifah Kasih S; Emi Rahmawati (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Early Childhood Education (PAUD) is an embryo of children's education in shaping a generation of people who are superior and dignified. Education provided to children aged 0-6 years primarily introduces physical activity to stimulate the child's motoric development, affection and introduce the process of socializing to children. Considering the importance of PAUD, the curriculum 2013 PAUD has now been developed, where previously there was no specific curriculum that could be used in the learning process in PAUD. Applying the curriculum 2013, the teachers still did not have enough capacity to be able to translate the concepts of the curriculum into the learning process. Therefore, training was carried out in an effort to increase capacity in the application of the Curriculum 2013 PAUD. The analytical method used is descriptive analysis and inference. The result of this activity is that there is a change in knowledge about the 2013 PAUD curriculum for the training participants. Participants give evaluators on the implementation of training in general is good. Outcome of this training the participants are required to disseminate the curriculum 2013 PAUD material